European food security between geopolitical shocks, productivity renewal and sustainability goals: current and future perspectives of Common Agricultural Policy - Ciccone, Mariassunta (Przegląd Prawa Rolnego, 2026)
Given the uncertainty that characterises agricultural markets and is exacerbated by the repercussions of the current energy crisis and other disruptions affecting the agri-food supply chain, expectations for the future Common Agricultural Policy (CAP) are particularly high. The CAP is expected to contribute to long-term food security. This paper analyses how the EU intends to prioritise strengthening its internal productive capacity, which is considered a strategic instrument for safeguarding European interests. Within this framework, the focus is on the future CAP (2028–2034), which will be required to pursue the objectives established by Article 39 of the Treaty on the Functioning of the European Union by providing more targeted and efficient support to farmers, while striking a balance between more flexible environmental requirements and more adequate economic incentives. Subsequently, the paper examines some of the provisions proposed in the Proposal for the modification of the Common Market Organisation, which are aimed at establishing strategic food stocks to improve preparedness and crisis management in the event of threats to food security. Finally, while the CAP plays a pivotal role, the paper also considers the new Fertilisers Action Plan and trade agreements between the EU and third countries, which aim to strengthen the resilience and competitiveness of the European economy as a whole.